Novel phenotype of aortic root dilatation and late‐onset metabolic decompensation in a patient with TMEM70 deficiency. Issue 5 (7th February 2023) - Mackay, Laura; Gijavanekar, Charul; Streff, Haley; Price, Jack F.; Elsea, Sarah H.; Scaglia, Fernando
Abstract: TMEM70 deficiency causing mitochondrial complex V deficiency, nuclear type 2 (MIM: 614052) is the most common nuclear encoded defect affecting ATP synthase and has been well described in the literature as being characterized by neonatal or infantile onset of poor feeding, hypotonia, lethargy, respiratory compromise, heart failure, lactic acidosis, hyperammonemia, and 3‐methylglutaconic aciduria progressing to a phenotype of developmental delay, failure to thrive, short stature, nonprogressive cardiomyopathy, microcephaly, facial dysmorphisms, hypospadias, persistent pulmonary hypertension of the newborn, and Wolff–Parkinson–White syndrome, as well as metabolic crises followed by developmental regression. The patient with TMEM70 deficiency herein reported has the unique presentation of aortic root dilatation, differing facial dysmorphisms, and no history of neonatal metabolic decompensation or developmental delay, as well as a plasma metabolomics signature, including elevated 3‐methylglutaconic acid, 3‐methylglutarylcarnitine, alanine, and lactate, in addition to the commonly described increased 3‐methylglutaconic acid on urine organic acid analysis that helped aid in the diagnostic interpretation of variants of uncertain significance in TMEM70 .